GENDER INJUSTICE TOWARDS THE MAIN CHARACTER IN THE NOVEL A SPARK OF LIGHT BY JODI PICOULT - Sulistya Afriliani (Journal Albion : Journal of English Literature, Language, and Culture, 2023)
This thesis analyzes gender injustice experienced by the female main character by applying qualitative descriptive analysis as the method in this research. The main data source used in this research is the novel A Spark of Light by Jodi Picoult. The research finding posits that the main character experiences gender injustice in the form of violence and stereotypes because of her decision to commit abortion. Another finding also indicates that abortion is still socially and culturally perceived as a negative action that should not be done by a woman.